Relationships between nonalcoholic fatty liver disease and polycystic ovary syndrome - E.H. Manzhalii; T.F. Tatarchuk; T.M. Tutchenko; N.V. Kosei; R.O. Mnevets (Publishing House TRILIST, 2023)
Polycystic ovary syndrome (PCOS) and non-alcoholic fatty liver disease (NAFLD) are two common non-infectious pathologies. Their frequency and medico-social significance have increased significantly over the past decades and reflect the effects of radical changes in human lifestyle on human health in a transgenerational aspect. Due to absence a complete understanding of the etiology and pathogenesis of PCOS and NAFLD, modern medicine still does not have etiopathogenetic methods of treating these frequent diseases. Considering epidemiological and pathogenetic data PCOS and NAFLD can be regarded as related pathologies, which creates the prospect of improving the effectiveness of their management if the joint approach to scientific research and implementation of their results in medical practice is applied. The purpose of the review is to summarize the current scientific data on the common pathophysiological and clinical relationships between PCOS and NAFLD, which can contribute to improving the effectiveness management of both diseases. Pathogenetic relationships between PCOS and NAFLD are bidirectional. According to current data, it seems possible to consider PCOS as a significant risk factor for the development of NAFLD in women of reproductive age both in the presence of excess weight and with normal body weight. As is known, that liver is involved in the clearance of androgens by the formation of sex steroid-binding globulin, as well as in the inactivation of insulin. Disruption of these metabolic processes due to liver pathology can lead to the development or strengthening of biochemical and clinical hyperandrogenism and the development of hyperinsulinemia and insulin resistance (IR). Conclusions. The presence of fatty liver and especially steatohepatitis deepens the hormonal disorders inherent in PCOS (primarily, an increase of free androgens, IR and ovulatory dysfunction), as well as potentiates and accelerates the development of cardiometabolic complications, including atherogenic dyslipidemia, dysglycemia, metabolic syndrome and cardiovascular complications. Early detection of NAFLD in women with PCOS, regardless of the presence of obesity, may improve the effectiveness of PCOS management and prevention of its cardiometabolic risks.